Current tobacco use and its associated factors among adults in Georgia: findings from Non-Communicable Disease Risk Factors STEPS Survey Georgia 2016 - Nino Maglaklelidze; Lela Sturua; Amiran Gamkrelidze; Mariam Maglakelidze (Tobacco Induced Diseases, 2018)
Background Tobacco surveys of past decades show that tobacco use prevalence is high in Georgia; According to nationwide Noncommunicable Diseases (NCDC) Risk Factors STEPS Survey 2010 30% of adult population are current tobacco users. Another Nationwide Tobacco Survey 2014 reported 28% of tobacco use prevalence among Georgian adults. However, there has been relatively little progress in systematic study of the factors associated with this high tobacco use. The current study aimed to assess the prevalence of tobacco use and its associated sociodemographic, behavioral and environmental factors in Georgia.